A Comprehensive Study of Ceramic Matrix Composites for Space Applications - S. Dhanasekar; Arul Thayammal Ganesan; Taneti Lilly Rani; Venkata Kamesh Vinjamuri; Medikondu Nageswara Rao; E. Shankar; null Dharamvir; P. Suresh Kumar; Wondalem Misganaw Golie (Advances in Materials Science and Engineering)
Ceramic matrix composites (CMCs) have grown in popularity as a material for a range of high as well as protection components, increasing the need to better understand the impacts of multiple machining methods. It is primarily composed of ceramic fibers embedded in the matrix. Ceramic materials, especially carbon fibers and carbon were used to create the matrix and fibers. These ceramics include a huge variety of non-metallic inorganic materials that are regularly utilized under high temperatures. The aircraft industry became revolutionized by this unique combination of materials, which made parts better resistant under extreme conditions as well as lighter than the earlier technology. The development, properties, and production of ceramic matrix composites, as well as space applications, are discussed in this article. Ceramic materials have an interesting set of properties, including great strength and stiffness under extremely high temperatures, chemical inertness, low density, etc. In CMC, ceramics are used in the matrix as well as reinforcement. The matrix material keeps things running smoothly while the reinforcement delivers unique special properties. Ceramic matrix composites are developed for applications that required high thermal and mechanical characteristics, which include nuclear power plants, aircraft, chemical plants, space structures, and transportation services. Even though advanced aircraft relies on high-performance propulsion systems, improving the total impulses over the total mass ratio for rocket engines becomes essential for improving their performance that demands reduced engine structural weight as well as higher component heat resistance. The evolution of new ultra-high-temperature composites having high-temperature resistance as well as low density that a substitute super alloy and refractory metal material has become so essential and laid the foundation for high-performance engine design. The benefits of continuous fiber- reinforced CMC with high-temperature engine designs have long been recognized as a better measure of a country’s ability to design and produce spacecraft, modern aircraft, and weapons. Ceramic matrix composites materials are used in various aircraft type engines, aircraft brake disks, high-temperature gas turbines components, slide bearing components, hot gas duct, flame holders and components for burners are made by using oxide CMCs.